“Woman Is The Nigger Of The World”. Una aproximación a la ruta contracultural de Lennon-Ono - Molinari Morales, Tirso Anibal (2018)
An approach is intended from the interactionist sociology, as well as the cognitive linguistics, to J. Lennon and Y. Ono’s both aesthetically-popular and political countercultural position particularities, based on the claim that combines simultaneously feminism and the struggle against racism in a metaphorical way, and in the early 70s, it is anticipated to expert views from the social sciences, mainly Latin American ones, that systematise approaches, from the early 90s, where racism and ethnicity with patriarchy are correlated from ethnic-critical theoretical perspectives basically linked to postcolonial studies, the so-called coloniality of power and researches into subalternity.